ETF arbitrage: Intraday evidence - Marshall, Ben R.; Nguyen, Nhut H.; Visaltanachoti, Nuttawat (Journal of Banking & Finance, 2013)
We use two extremely liquid S&P 500 ETFs to analyze the prevailing trading conditions when mispricing allowing arbitrage opportunities is created. While these ETFs are not perfect substitutes, our correlation and error correction results suggest investors view them as close substitutes. Spreads increase just before arbitrage opportunities, consistent with a decrease in liquidity. Order imbalance increases as markets become more one-sided and spread changes become more volatile which suggests an increase in liquidity risk. The price deviations are followed by a tendency to quickly correct back towards parity.